2021
DOI: 10.1017/s0950268821002077
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of SARS-CoV-2 transmission in educational institutions, August to December 2020, Germany

Abstract: Article's main points  1-2% of close contacts to a COVID-19 case in educational institutions become infected.  Transmission-risk was tripled in day-care centres.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
4
10
0
1
Order By: Relevance
“…Reported SAR values from other school outbreak investigations from the same period that used comparable methodology ranged between 0.0 and 6.5% [9][10][11][12][13][14][15][16][17][18]. The majority of the secondary cases in these studies were asymptomatic (47.8-66.6%), in line with our observations [10,17].…”
Section: Discussionsupporting
confidence: 88%
“…Reported SAR values from other school outbreak investigations from the same period that used comparable methodology ranged between 0.0 and 6.5% [9][10][11][12][13][14][15][16][17][18]. The majority of the secondary cases in these studies were asymptomatic (47.8-66.6%), in line with our observations [10,17].…”
Section: Discussionsupporting
confidence: 88%
“…Reported (SAR) values from other school outbreak investigations from the same period that used comparable methodology ranged between 0.0 to 6.5% [9][10][11][12][13][14][15][16][17][18]. The majority of the secondary cases in these studies were asymptomatic (47.8%-66.6%), in line with our observations [10,17].…”
Section: Discussionsupporting
confidence: 88%
“…Whereas increased age of students was associated with a higher risk of infection, as previously shown [ 17 , 19 ], this effect appeared reduced with the alpha variant (phase 4) and is likely to have reduced further with even more transmissible variants [ 15 ].…”
Section: Discussionmentioning
confidence: 70%
“…In a systematic review [16], we showed that during phases with low population incidence, there is no increased risk of infection in students or school staff; however, with increasing infection dynamics in the population, the risk of infection in students and staff increases. In Germany and Europe, studies on school transmission risk and contribution to overall transmission in the population are based on geographically and temporally limited data [3,[17][18][19][20], with few exceptions [21]. Results do not show longitudinal changes in the same dataset, neither do reports from seroprevalence studies on infection risk in students [15].…”
Section: Introductionmentioning
confidence: 99%